ACCOUNTING, ANALYSIS AND AUDITING OF INFORMATION REGARDING TANGIBLE ASSETS IN THE ROMANIAN ECONOMIC ENTITIES - RUS, Luminița; BELENEȘI, Mărioara; GHERAI, Dana Simona (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2016)
Unlike the companies who are incorporated with the purpose of obtaining profit, the non-profit organizations and public institutions are functioning based on various sources of funding. The present work aims at the recognition in the accounts of the fixed assets amounted to those three types of entities. In this process we have started to study the accounting rules applicable to these entities, as well as specialized works of recent date. The aspects studied and presented with regard to the definition, initial evaluation and subsequent evaluation were followed by a comparison of their types for the entities subject to study, and then present a comparative statement of recording in the accounts of major operations relating to the fixed assets. Finally, we present some information regarding the indicators of financial and economic analysis that uses the value of the fixed assets and some aspects which are examined by the auditor in his objective opinion regarding the tangible assets. It may be noted that tangible assets occupies an important place in the life of an entity and that the reflection of them in their accounting provides the same information, even though the accounting formulas used are different. But what makes the difference in accounting is closely related to the specific of the economic entity analyzed and the information they must submit to users of accounting information.